Effects of Ethanol Exposure During Adolescence or Adulthood on Locomotor Sensitization and Dopamine Levels in the Reward System - Carrara-Nascimento, Priscila Fernandes; Hoffmann, Lucas Barbosa; Flório, Jorge Camilo; Planeta, Cleopatra Silva; Camarini, Rosana (Frontiers in Behavioral Neuroscience, 2020)
Behavioral sensitization is a process of neuroadaptation characterized by a gradual increase in motor behaviors. The major neural substrates involved in the behavioral sensitization lie on the dopaminergic mesocorticolimbic pathway, which is still under development during adolescence. To investigate age-differences in ethanol behavioral sensitization and dopamine levels in distinct brain regions of the reward system, adolescent and adult mice were repeatedly pretreated with saline or ethanol (2.0 g/kg i.p.) during 15 consecutive days and challenged with saline or ethanol 5 days after pretreatment. Dopamine and its metabolites were measured in tissue samples of the prefrontal cortex (PFC), nucleus accumbens (NAc) and striatum by HPLC analysis. While repeated ethanol administration resulted in the development of locomotor sensitization in both adult and adolescent mice, only the adults expressed sensitization to a subsequent ethanol challenge injection. Neurochemical results showed reduced dopamine levels in adolescents compared to adults. Specifically, mice pretreated with ethanol during adolescence displayed lower dopamine levels in the PFC compared to the respective adult group in response to an ethanol challenge injection, and preadolescent mice exhibited lower dopamine levels in the NAc following an acute ethanol treatment compared to adults. These findings suggest that adolescent mice are not only less sensitive to the expression of ethanol-induced sensitization than adults, but also show lower dopamine content after ethanol exposition in the PFC and NAc.